Manajemen Strategi Pemerintah Dalam Peningkatan Ketahanan Pangan - Nafisah Ikbar Fadhilah; Maulana Rifai; Prilla Marsingga (Universitas Musamus, Merauke, Papua, 2021)
Food security is a condition where food is fulfilled for all people at any time of which quality isguaranteed, nutritious, safe from harmful substances and is evenly distributed and affordable to all. Forthis reason, the food diversification program is implemented in one of the Women's Farmer Groups(KWT) in Cilewo Village, Telagasari District because KWT is the most active farmer group in Karawang.The purpose of this study was to determine the government's strategic management in increasing foodsecurity through food diversification based on local resources by implementing sustainable food gardens(P2L) in Asih Munggaran's Women Farmers Group (KWT) This study uses a descriptive method with aqualitative approach, namely the type of research that seeks to describe a phenomenon in accordancewith what happens in the field which produces descriptive data in the form of words, written documents,and pictures. Data collection techniques used are through literature and field studies (interviews,observation and documentation). Researchers found that the existence of a strategy for diversifying foodconsumption in Karawang Regency has formed an achievement of diverse food patterns in the communityand fostered the spirit of creativity of the members of Asih Munggaran's Women Farmers Group (KWT)from the use of sustainable food yards so that they can help meet household income. farm household.However, the use of yards is still dominated by plantation / agricultural land and has not been maximizedfor livestock.